The Sanad of Jihadi Figures in the Global Terrorism Network - Mala, Faiqotul; Ema Marhumah; Agung Danarta (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This article sheds light on how the radical ideology embraced by terrorist actors in Indonesia is connected to the radical ideology of jihadi figures in the world? This study utilizes a multidisciplinary approach to map the ideological evolution and interconnections among jihadi figures in Indonesia and globally. It integrates historical analysis and ideological mapping to provide a comprehensive understanding. Using sanad-based intellectual history theory done by profiling the jihadi figures (from Muhammad bin Abdul Wahhab to Aman Abdurrahman) and sanad analysis of their ideological and political views, this article finds the connection between the Indonesian Jihadi figures and the global jihadi figures. Also, this article sees that the radical ideology in Indonesia is transmitted through a convincing chain of sanad from global jihadi figures. This transmission, at the ends, proves the existence of global radicalism indoctrination.